Exploring the Role of Consumer Trust in Mediating the Relationship between Commitment and Satisfaction in Yogyakarta - Isra Kuncoro (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
This study aims to examine the impact of consumer commitment on consumer satisfaction, mediated by consumer trust, within the cosmetics industry in Yogyakarta. Using a quantitative approach with Structural Equation Modeling (SEM) based on Partial Least Squares (PLS), the study involved 121 respondents selected through purposive sampling. Data was collected via a questionnaire measuring three main variables: consumer commitment, consumer trust, and consumer satisfaction using a 1-5 Likert scale. The analysis results indicate that consumer commitment significantly affects consumer trust, which in turn influences consumer satisfaction. Although the direct impact of commitment on satisfaction is not significant, consumer trust was found to significantly mediate the relationship between commitment and satisfaction. This study offers important implications for cosmetics companies to focus more on developing consumer commitment and trust to enhance customer satisfaction and loyalty. Future research is recommended to broaden the scope by adding other variables, such as service quality, and testing the findings in different locations and products to improve the generalization of the results.